Versatile routes to functional RAFT chain transfer agents through the Passerini multicomponent reaction - Pearce, Amanda K.; Travanut, Alessandra; Couturaud, Benoit; Taresco, Vincenzo; Howdle, Steven M.; Alexander, Morgan R.; Alexander, Cameron (American Chemical Society, 2017)
The widespread adoption of RAFT polymerization stems partly from the ease and utility of installing a functional chain transfer agent onto the ends of the generated polymer chains. In parallel, the Passerini multicomponent reaction offers great versatility in converting a wide range of easily accessible building blocks to functional materials. In this work, we have combined the two approaches such that a single, commonly available, RAFT agent is used in Passerini reactions to generate a variety of multifunctional RAFT chain transfer agents containing ester linkages. Reactions to generate the multifunctional RAFT agents took place under mild conditions and in good yields. The resulting Passerini-RAFT agents were able to exert control over radical polymerization to generate materials of well-defined molecular weights and dispersity. Furthermore, the presence in these polymer cores of ester and amide functionality through the Passerini chemistries, provided regions in the materials which are inherently biodegradable, facilitating any subsequent biomedical applications. The work overall thus demonstrates a versatile and facile synthetic route to multi functional RAFT chain transfer agents and biodegradable polymers.